On the Ionospheric Disturbances in New Zealand and Australia Following the Eruption of the Hunga Tonga‐Hunga Ha'apai Volcano on 15 January 2022 - Peng Chen; Mingzhu Xiong; Rong Wang; Yibin Yao; Fucai Tang; Hao Chen; Liangcai Qiu (Space Weather)
Abstract The Hunga Tonga‐Hunga Ha'apai (hereafter HTHH) submarine volcano erupted at 04:14:45 UT on 15 January 2022, causing ionospheric disturbances. This paper uses carrier phase observations from GNSS tracking stations in New Zealand and Australia to calculate the vertical total electron content. At 06:10, the ground‐based GNSS tracking station in New Zealand observes a maximum amplitude of 2.26 TECU anomaly caused by a mesoscale traveling ionospheric disturbance (MSTID) with a wavelength of 200–250 km, a period of 6–13 min, and a maximum propagation velocity of 330 m/s. The anomaly developed with time along the north‐south island direction toward the south island and lasted for about three and a half hours, with the ionosphere returning to pre‐eruption levels after 09:50, indicating a correlation between ionospheric activity and volcanic eruption. An ionospheric anomaly caused by an MSTID was also observed off the east coast of Australia around 08:11, with a maximum amplitude of 3.17 TECU and a maximum propagation velocity of 356 m/s. The ionospheric anomaly in Australia spreads out in a plane. In the process of propagation, it continuously impacts the area it passes through, and the entire anomaly process lasts for more than 7 hr. Still, the anomalous propagation velocities are more significant than in New Zealand, indicating that the Lamb waves excited by the eruption of the HTHH submarine volcano are directional in propagation speed; westward travels faster than southward. This finding will provide more references for scholars to study the mechanism and characteristics of anomaly propagation.